THE IMPORTANCE OF INTERDISCIPLINARY TEACHING PRACTICES IN DEVELOPING LANGUAGE SKILLS - Temirova , Sayyora; Shukurboyeva, Khonzoda (GOLDEN BRAIN, 2024)
This article explores the role of interdisciplinary teaching practices in developing language skills. It highlights real-life examples such as sustainability fairs, TED Talks, and role-playing activities to demonstrate the benefits of combining disciplines in language education. The article discusses practical applications, challenges, and solutions, emphasizing the potential of interdisciplinary approaches to provide meaningful and engaging learning experiences